The Influence of Digital Marketing, Destination Image, and Tourist Attraction on Revisit Intention through Tourist Satisfaction at Bogor Botanical Gardens - Reliantama Tanamas, Randy; Oswari, Teddy (Equator Journal of Management and Entrepreneurship (EJME), 2026)
This study aims to examine the influence of digital marketing, destination image, and tourist attraction on revisit intention through tourist satisfaction at the Bogor Botanical Gardens. This study uses a quantitative method by collecting data through an online questionnaire distributed to 150 tourists who have visited the Bogor Botanical Gardens. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results of the study indicate that digital marketing does not have a significant effect on revisit intention, while destination image and tourist attraction have a significant effect on revisit intention. Digital marketing, destination image, and tourist attraction have a significant effect on tourist satisfaction. Tourist satisfaction also has a significant effect on revisit intention. Furthermore, digital marketing, destination image, and tourist attraction influence revisit intention indirectly through tourist satisfaction. This research contributes to the development of literature on digital marketing, destination image and tourist attractions, as well as practical contributions for Bogor Botanical Gardens managers in increasing return visit interest through tourist satisfaction.